Traumatic anterior dislocation of the crystalline lens in a quite eye. (October 2019) - Gurnani, Bharat; Kaur, Kirandeep; Gireesh, Prasanth
Blunt ocular trauma is the one of the commonest cause of anterior dislocation of the crystalline lens. We present a case who presented with anterior dislocation of the crystalline lens, vitreous prolapse, and acute painful vision loss in left eye following blunt trauma. The patient was managed with antiglaucoma medications, automated anterior vitrectomy, and surgical extraction of dislocated lens with a delayed pars plana vitrectomy and transcleral fixation of crystalline lens.